Preparation of coal-tar pitch carbon and carbon nitride composite materials and optoelectronic sensing applications
Patent Information
- Application Number
- CN202611065281.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-16
AI Technical Summary
[0007]本发明的主要目的在于提供煤沥青碳及氮化碳复合材料制备及光电传感应用,提供的方法制得的复合材料不仅实现了煤化工固废的高值化利用,且具有优异的光电传感性能,解决了单一g-C3N4导电性差、光生载流子复合快以及现有传统传感器难以同步、高选择性检测多种重金属离子的难题
[0016] Compared with existing technologies, this invention has the following advantages: It is the first time that coal tar pitch-based carbon materials have been applied to the field of photoelectric sensing, significantly reducing material costs compared to commercial carbon materials and realizing the transformation of coal chemical solid waste into valuable resources. Through in-situ doping with urea and sodium hypophosphite, abundant nitrogen- and phosphorus-containing functional groups are introduced onto the surface of coal tar pitch-derived carbon. This enhances hydrogen bonding and π-π interactions between the carbon material and g-C3N4, forming a tight and stable heterojunction interface. Furthermore, it modulates the Fermi level and band structure of the carbon material, significantly reducing the charge transfer barrier at the heterojunction interface and effectively suppressing the recombination of photogenerated electron-hole pairs. By fully utilizing the strong complexing ability of amino groups on the g-C3N4 surface for heavy metal ions and the synergistic coordination of oxygen- and nitrogen-containing functional groups on the coal tar pitch-derived carbon surface, a dual-mechanism sensing model of "surface complexation-synergistic coordination" is constructed. This allows for the sensing of Pb without the need for expensive biological enzymes or noble metal probes. 2+ Cd 2+ Hg 2+ Highly selective synchronous detection with strong anti-interference capability (for common coexisting ions such as K+). + Na + Ca 2+ Mg 2+ Fe 3+ (And does not produce significant interference). Furthermore, this invention introduces trace amounts of bismuth ions into the detection substrate for in-situ co-deposition, effectively eliminating Cd by utilizing the excellent electrocatalytic activity and alloying effect of the bismuth film. 2+ and Pb 2+ The overlapping interference of dissolution peaks, which is prone to occur on conventional carbon-based electrodes, was overcome to achieve superior peak separation and a wider electrochemical detection window. The photoelectrochemical sensor constructed based on this composite material exhibits high sensitivity to target heavy metal ions under a photocurrent quenching mechanism. Under optimized conditions, Pb... 2+ The detection limit is 0.1 µM, and the linear range is 0.1–1 µM; Cd 2+ Detection limit 0.4 µM, linear range 0.4–1 µM; Hg 2+ The detection limit is 0.05 µM, and the linear range is 0.05–0.5 µM.
Smart Images

Figure CN122916096A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the preparation of coal tar pitch carbon and carbon nitride composite materials and their photoelectric sensing applications, belonging to the field of photoelectrochemical sensing materials and their preparation technology. Background Technology
[0002] With the rapid development of modern industry, heavy metal pollution in water bodies, such as lead (Pb), cadmium (Cd), and mercury (Hg), has become a global environmental problem. Heavy metal ions are non-degradable and bioaccumulate, posing a serious threat to ecosystems and human health. Traditional heavy metal detection methods (such as inductively coupled plasma mass spectrometry and atomic absorption spectrometry), while highly sensitive, have limitations including expensive instruments, complex pretreatment processes, and difficulty in achieving rapid on-site analysis.
[0003] Photoelectrochemical (PEC) sensors have attracted much attention due to their separation of excitation and detection signals, low background noise, and high sensitivity. The basic principle of photoelectrochemical sensors is to use semiconductor nanomaterials as electrode materials, which generate photogenerated electron-hole pairs under external light irradiation. In the presence of heavy metal ions to be measured, the ions undergo specific adsorption or complexation with active sites on the material surface, which leads to a regular change in the detection current, affecting the interfacial charge transfer efficiency and causing a regular change in the photocurrent, thereby reflecting the concentration of heavy metal ions.
[0004] Graphitic carbon nitride (g-C3N4), as a non-metallic visible-light responsive semiconductor, possesses a unique two-dimensional layered structure, a large specific surface area, and abundant surface amino functional groups, making it an ideal material for adsorbing and detecting heavy metal ions. However, single g-C3N4 suffers from fatal defects such as poor intrinsic conductivity and easy recombination of photogenerated electron-hole pairs, severely limiting its photoelectric conversion efficiency and sensing sensitivity. To overcome these defects, researchers have attempted to composite g-C3N4 with various carbon materials (such as graphene, graphene oxide, carbon nanotubes, and biochar), utilizing the high conductivity of carbon materials to construct electron transport channels to suppress the recombination of photogenerated carriers. For example, CN118122391A discloses a reduced graphene oxide / g-C3N4 composite material for photocatalytic degradation of dyes and antibiotics; CN114260020A discloses a carbon nitride-modified carbon nanotube composite material for removing phenolic pollutants from aqueous solutions. However, these carbon materials are costly and have complex preparation processes, limiting their large-scale application.
[0005] On the other hand, heteroatom doping (such as nitrogen, phosphorus, boron, and sulfur) is an important means of controlling the electronic structure and surface chemical properties of carbon materials, and has been widely studied in the fields of electrocatalysis and energy storage. Existing literature reports that nitrogen doping can introduce nitrogen-containing functional groups such as pyridine nitrogen, pyrrole nitrogen, and graphitic nitrogen into carbon materials, thereby controlling the Fermi level and work function; phosphorus doping, due to its larger atomic radius and lower electronegativity, can introduce structural defects and positively charged sites into the carbon framework. However, existing heteroatom-doped carbon materials are mostly used in oxygen reduction reactions (ORR), supercapacitors, and lithium-ion batteries, and their application in photoelectrochemical sensing remains very limited. In particular, nitrogen-phosphorus dual doping, compared to single-element doping, can produce a synergistic effect: nitrogen doping increases the electron density of carbon materials, while phosphorus doping introduces structural defects and localized polarization centers; the combined effect of both can further optimize the band structure and surface polarity of carbon materials. Currently, a few studies have used nitrogen and phosphorus co-doped carbon materials for electrocatalysis (such as CN115995571A, a method for preparing and applying heteroatom-doped porous carbon materials) or energy storage (such as CN115663152B, a hard carbon-nitrogen-phosphorus co-doped nano-carbon composite material and its preparation method), but there are no reports on using nitrogen and phosphorus co-doped coal tar pitch-derived carbon combined with g-C3N4 for photoelectrochemical detection of heavy metal ions.
[0006] Coal tar pitch, a solid waste product from coal chemical industry, is rich in polycyclic aromatic hydrocarbons. Through rational carbonization activation and heteroatom doping, it can be transformed into coal tar pitch-derived carbon, which possesses a well-developed porous structure and nitrogen and phosphorus doping characteristics. This material is extremely low in cost and exhibits excellent conductivity and abundant surface active sites. However, how to organically combine the conductivity and carrier advantages of coal tar pitch-derived carbon with the photoelectric activity of g-C3N4 through rational structural design to construct a composite photoelectric sensing material with a synergistic enhancement effect remains a topic requiring further exploration. Currently, there are no reports on the use of coal tar pitch-derived carbon and g-C3N4 composites for photoelectrochemical detection of heavy metal ions. Summary of the Invention
[0007] The main objective of this invention is to provide a method for preparing carbon and carbon nitride composite materials and their photoelectric sensing applications. The composite material prepared by the method not only realizes the high-value utilization of coal chemical solid waste, but also has excellent photoelectric sensing performance, solving the problems of poor conductivity of single g-C3N4, fast recombination of photogenerated carriers, and the difficulty of simultaneous and highly selective detection of multiple heavy metal ions by existing traditional sensors.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is: a preparation method for coal tar pitch carbon and carbon nitride composite materials and their photoelectric sensing applications, comprising the following steps: Step 1: Preparation of nitrogen-phosphorus co-doped coal tar pitch-derived carbon: Coal tar pitch, potassium carbonate, potassium chloride, urea, and sodium hypophosphite are mixed and thoroughly ground, then placed in a tube furnace and calcined at high temperature under an inert atmosphere. After natural cooling, the product is removed and washed alternately with deionized water and 95% ethanol by centrifugation until the supernatant is colorless. Finally, it is freeze-dried to obtain nitrogen-phosphorus co-doped coal tar pitch-derived carbon. Step 2, preparation of g-C3N4 nanosheets: The nitrogen-containing precursor is placed in a muffle furnace and thermally polycondensed and calcined at a specific temperature. The resulting bulk material is then ground and ultrasonically exfoliated in water to obtain a two-dimensional g-C3N4 nanosheet dispersion. Step 3, assembly of composite materials: Disperse the coal tar-derived carbon obtained in Step 1 in deionized water and adjust the pH value to 3-4 to make its surface positively charged; adjust the pH value of the g-C3N4 dispersion obtained in Step 2 to 9-10 to make its surface negatively charged; mix the two and stir thoroughly with ultrasonication, centrifuge, wash and dry to obtain the coal tar-derived carbon / g-C3N4 composite nanomaterial.
[0009] Furthermore, in step one, the mass ratio of coal tar pitch, potassium carbonate, and potassium chloride is 1:3:5, and 0.5 g of urea and 1 g of sodium hypophosphite are added for every 0.25 g of coal tar pitch; the mixing and grinding time is 30 minutes.
[0010] Furthermore, in step one, the high-temperature calcination treatment involves heating to 700°C at a heating rate of 5°C / min under argon protection and holding at that temperature for 2 hours; the ethanol used for washing is 95% ethanol.
[0011] Furthermore, in step two, the nitrogen-containing precursor is melamine or urea.
[0012] Furthermore, the composite material comprises coal tar pitch-derived carbon and g-C3N4 nanosheets uniformly bonded to its surface, wherein the mass ratio of g-C3N4 to coal tar pitch-derived carbon is (5~9):(1~5), preferably 7:3.
[0013] Furthermore, as an application of electrode materials in the construction of photoelectrochemical sensors, photoelectrochemical sensors include working electrodes, counter electrodes, and reference electrodes.
[0014] Furthermore, the method for preparing the working electrode includes: ultrasonically dispersing the composite nanomaterial, anhydrous ethanol, deionized water and Nafion solution into a uniform slurry, drop-coating it onto the cleaned FTO glass surface, and drying it at room temperature.
[0015] Furthermore, photoelectrochemical sensors are used to detect Pb in water. 2+ Cd 2+ Hg 2+Applications of heavy metal ions.
[0016] Compared with existing technologies, this invention has the following advantages: It is the first time that coal tar pitch-based carbon materials have been applied to the field of photoelectric sensing, significantly reducing material costs compared to commercial carbon materials and realizing the transformation of coal chemical solid waste into valuable resources. Through in-situ doping with urea and sodium hypophosphite, abundant nitrogen- and phosphorus-containing functional groups are introduced onto the surface of coal tar pitch-derived carbon. This enhances hydrogen bonding and π-π interactions between the carbon material and g-C3N4, forming a tight and stable heterojunction interface. Furthermore, it modulates the Fermi level and band structure of the carbon material, significantly reducing the charge transfer barrier at the heterojunction interface and effectively suppressing the recombination of photogenerated electron-hole pairs. By fully utilizing the strong complexing ability of amino groups on the g-C3N4 surface for heavy metal ions and the synergistic coordination of oxygen- and nitrogen-containing functional groups on the coal tar pitch-derived carbon surface, a dual-mechanism sensing model of "surface complexation-synergistic coordination" is constructed. This allows for the sensing of Pb without the need for expensive biological enzymes or noble metal probes. 2+ Cd 2+ Hg 2+ Highly selective synchronous detection with strong anti-interference capability (for common coexisting ions such as K+). + Na + Ca 2+ Mg 2+ Fe 3+ (And does not produce significant interference). Furthermore, this invention introduces trace amounts of bismuth ions into the detection substrate for in-situ co-deposition, effectively eliminating Cd by utilizing the excellent electrocatalytic activity and alloying effect of the bismuth film. 2+ and Pb 2+ The overlapping interference of dissolution peaks, which is prone to occur on conventional carbon-based electrodes, was overcome to achieve superior peak separation and a wider electrochemical detection window. The photoelectrochemical sensor constructed based on this composite material exhibits high sensitivity to target heavy metal ions under a photocurrent quenching mechanism. Under optimized conditions, Pb... 2+ The detection limit is 0.1 µM, and the linear range is 0.1–1 µM; Cd 2+ Detection limit 0.4 µM, linear range 0.4–1 µM; Hg 2+ The detection limit is 0.05 µM, and the linear range is 0.05–0.5 µM. Attached Figure Description
[0017] Figure 1 The X-ray diffraction (XRD) patterns of Example 1 (coal tar pitch-derived carbon / g-C3N4), Comparative Example 1 (g-C3N4), and Comparative Example 2 (coal tar pitch-derived carbon) of the present invention are shown below. Figure 2The images are scanning electron microscope (SEM) images of Example 1 (coal tar pitch-derived carbon / g-C3N4), Comparative Example 1 (g-C3N4), and Comparative Example 2 (coal tar pitch-derived carbon) of the present invention. Figure 3 The sensor constructed for Embodiment 1 of this invention uses square wave stripping voltammetry (SWASV) to measure Pb. 2+ Cd 2+ Hg 2+ Simultaneous detection of dissolution peak curves; Figure 4 The sensor constructed for Embodiment 1 of this invention uses square wave stripping voltammetry (SWASV) to measure Hg. 2+ Dissolution peak curve of mercury ions detected alone; Figure 5 The sensors constructed for Comparative Example 1 (g-C3N4) and Comparative Example 2 (coal tar pitch-derived carbon) of the present invention were used to detect Pb using square wave stripping voltammetry (SWASV). 2+ Cd 2+ Hg 2+ Simultaneous detection of dissolution peak curves; Figure 6 This is a schematic diagram of the process for preparing carbon derived from coal tar pitch. Detailed Implementation
[0018] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below with reference to the accompanying drawings.
[0019] Figure 1 In the composite material, the characteristic diffraction peaks of g-C3N4 are located at 2θ=21.6° and 26.5°, corresponding to the (100) and (002) planes of the layered g-C3N4 structure, respectively; the coal tar pitch-derived carbon exhibits a diffraction peak at 2θ=26.3°, corresponding to the C (111) plane. The composite material retains the characteristic peaks of both, indicating successful composite formation.
[0020] Figure 2 In Figure 2 a shows that pure g-C3N4 exhibits a plate-like aggregated structure; Figure 2 b shows that the coal tar pitch-derived carbon is in the form of irregular blocky particles with a porous surface; Figure 2 c shows that g-C3N4 nanosheets are uniformly loaded on the surface of coal tar pitch-derived carbon in the composite material, with no obvious agglomeration.
[0021] Figure 3 The strong characteristic peak around -0.25 V in the figure represents the dissolution peak of Bi3+ co-deposited in situ. 3+ With the assistance of Pb 2+ The dissolution peak is located at -0.67 V (vs. SCE), Cd 2+Located at -0.90 V, Hg 2+ At +0.37 V, the dissolution peaks of the three target ions are well separated and do not interfere with each other.
[0022] Figure 4 The dissolution peak is located at 0.37 V (vs. SCE) and shows good linearity.
[0023] Figure 6 The complete process route for producing coal tar pitch-derived carbon is demonstrated, which involves raw material preparation, mixing and grinding, high-temperature calcination, cleaning and drying.
[0024] Example 1: Preparation of composite nanomaterials Step 1: Preparation of nitrogen-phosphorus co-doped coal tar pitch-derived carbon: Weigh 0.25 g of coal tar pitch (softening point 100~115 ℃, ash content ≤0.3%), 0.75 g of potassium carbonate, and 1.25 g of potassium chloride, and add an additional 0.5 g of urea and 1 g of sodium hypophosphite. Mix thoroughly and grind for 30 minutes to obtain a mixed precursor. Then, place the mixed precursor in a tube furnace and heat to 700 ℃ at a heating rate of 5 ℃ / min under an argon atmosphere, and calcine at this temperature for 2 h. After naturally cooling to room temperature, remove the product and wash it sequentially with deionized water by centrifugation (8000 rpm, 10 minutes) until the supernatant is colorless (usually 5-8 washes). Finally, freeze-dry the washed product at -50 ℃ for 24 hours to obtain coal tar pitch-derived carbon with a nitrogen-phosphorus co-doped structure.
[0025] Step 2, Preparation of g-C3N4 nanosheets: 10 g of melamine was placed in a lidded alumina crucible and heated to 550 °C in a muffle furnace at a rate of 5 °C / min and held for 4 h. After natural cooling, a pale yellow block was obtained, which was then ground into powder. 1 g of powder was dispersed in 100 mL of deionized water and ultrasonically exfoliated for 4 h (ultrasonic power 240 W). Then, the unexfoliated large particles were removed by centrifugation at 3000 rpm for 10 minutes, and the supernatant was collected to obtain a g-C3N4 nanosheet dispersion.
[0026] Step 3, Preparation of coal tar pitch-derived carbon / g-C3N4 composite material: Weigh 70 mg g-C3N4 and 30 mg nitrogen-phosphorus co-doped coal tar pitch-derived carbon. Disperse the coal tar pitch-derived carbon in 100 mL of water and adjust the pH to 3-4 with 0.1 M HCl; adjust the pH of the g-C3N4 dispersion to 9-10 with 0.3% ammonia. Under magnetic stirring, slowly add the g-C3N4 dispersion to the coal tar pitch-derived carbon dispersion, and after the addition is complete, ultrasonically stir for 30 min. After naturally cooling to room temperature, centrifuge (6000 rpm, 10 min), wash the precipitate three times each with deionized water and 95% ethanol, and vacuum dry at 60 ℃ for 12 hours to obtain the composite material of this example (mass ratio of g-C3N4 to coal tar pitch-derived carbon is 7:3).
[0027] Example 2: Comparative Experiment with Different Composite Ratios Following the preparation method of Example 1, composite materials with mass ratios of 9:1, 7:3, and 5:5 were prepared by changing only the mass ratio of g-C3N4 to coal tar pitch-derived carbon in step 3. Sensors were constructed using the obtained materials according to the method of Example 3, and their performance was tested. The results showed that the composite material with a mass ratio of 7:3 exhibited the highest initial photocurrent (approximately 3.2 times higher than pure g-C3N4), and also showed the best performance for Pb. 2+ The response current change rate is the largest at (0.1 µM), therefore 7:3 is the preferred ratio.
[0028] Example 3: Construction and Detection of Photoelectrochemical Sensor Preparation of the working electrode: 10 mg of the composite material obtained in Example 1 was added to 25 µL of anhydrous ethanol, 25 µL of deionized water, and 15 µL of Nafion solution (5 wt%), and ultrasonically dispersed for 30 minutes to form a uniform slurry. 5 µL of the slurry was drop-coated onto cleaned FTO conductive glass (conductive side up, coating area approximately 1 cm × 1 cm), allowed to dry naturally at room temperature, and then vacuum-dried at 40 °C for 2 hours to obtain the working electrode.
[0029] Construction of the detection system: A three-electrode detection system was constructed using the prepared FTO / composite material electrode as the working electrode, a platinum sheet electrode as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode. The supporting electrolyte was a 0.1 M acetate buffer (pH 5.0) containing 100 µM bismuth nitrate. During the enrichment stage, bismuth ions and target heavy metal ions were co-deposited in situ on the electrode surface to form a bismuth film. The introduction of this bismuth film not only significantly distinguishes the dissolution peaks of cadmium and lead ions and avoids peak overlap, but also further improves the detection sensitivity of the sensor. Detection was performed using square wave anodic stripping voltammetry (SWASV): enrichment potential -1 V, enrichment time 120 s, resting time 10 s, followed by a forward square wave scan (potential range -1 V to 0.6 V, frequency 15 Hz, pulse amplitude 25 mV, step potential 2 mV). The light source was a 300 W xenon lamp with a power density of 100 mW / cm², vertically illuminating the working electrode surface.
[0030] Performance testing: Under optimal conditions, different concentrations of Pb were tested. 2+ Cd 2+ and Hg 2+ Standard solutions. Record the characteristic dissolution peak current values of each heavy metal ion and plot a standard curve.
[0031] Pb 2+ The dissolution peak is located at -0.67 V (vs. SCE), and the peak current shows a good linear relationship with the concentration in the range of 0.1~1 µM. The detection limit (S / N=3) is 0.1 µM.
[0032] Cd 2+ The dissolution peak is located at -0.90 V (vs. SCE), with a linear range of 0.4~1 µM and a detection limit of 0.4 µM.
[0033] Hg 2+ The dissolution peak is located at 0.37 V (vs. SCE), with a linear range of 0.05–0.5 µM. The regression equation is I(µA) = 49.8 C(µM) + 2.12, R0 2 = 0.993, detection limit 0.05 µM.
[0034] Simultaneous detection performance: In a solution containing 0.3 µM Pb 2+ 0.4 µM Cd 2+ and 0.1 µM Hg 2+ In the mixed solution, the three dissolution peaks were well separated (peak potential difference ≥ 1.2V) with no cross-interference.
[0035] Reproducibility and stability: Five sensors prepared in the same batch were used to test 0.5 µM Hg. 2+The relative standard deviation of the peak current was 5% during testing. After the sensor was stored at room temperature for 7 days, the initial photocurrent decay was less than 10%.
[0036] Comparative Example 1 (pure g-C3N4) The only difference between this comparative example and Example 1 is that coal tar pitch-derived carbon was not added; the sensor was constructed directly using the pure g-C3N4 nanosheet dispersion prepared in step 2, following the method in Example 3. Under the same detection conditions, the initial photocurrent of the pure g-C3N4 sensor was only about 20% of that of the composite material in Example 1, and for 0.1 µM Pb... 2+ The response current change rate is only about 36% of that of the composite material, and the detection limit is about 4 times that of the composite material.
[0037] Comparative Example 2 (Coal Tar-Derived Carbon) The only difference between this comparative example and Example 1 is that g-C3N4 is not added; the sensor is constructed directly using the coal tar pitch-derived carbon prepared in step 1, following the method in Example 3. Due to the lack of a photosensitive semiconductor, this electrode generates almost no photocurrent under illumination and cannot be used for photoelectrochemical detection.
[0038] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing coal tar pitch carbon and carbon nitride composite materials and their application in photoelectric sensing, characterized in that, Includes the following steps: Step 1: Preparation of nitrogen-phosphorus co-doped coal tar pitch-derived carbon: Coal tar pitch, potassium carbonate, potassium chloride, urea, and sodium hypophosphite are mixed and thoroughly ground, then placed in a tube furnace and calcined at high temperature under an inert atmosphere. After natural cooling, the product is removed and washed alternately with deionized water and 95% ethanol by centrifugation until the supernatant is colorless. Finally, it is freeze-dried to obtain nitrogen-phosphorus co-doped coal tar pitch-derived carbon. Step 2, preparation of graphitic carbon nitride (g-C3N4) nanosheets: The nitrogen-containing precursor is placed in a muffle furnace and thermally polycondensed and calcined at a specific temperature. The resulting bulk material is ground and then ultrasonically exfoliated in water to obtain a two-dimensional g-C3N4 nanosheet dispersion. Step 3, assembly of composite materials: Disperse the coal tar-derived carbon obtained in Step 1 in deionized water and adjust the pH value to 3-4 to make its surface positively charged; adjust the pH value of the g-C3N4 dispersion obtained in Step 2 to 9-10 to make its surface negatively charged; mix the two and stir thoroughly with ultrasonication, centrifuge, wash and dry to obtain the coal tar-derived carbon / g-C3N4 composite nanomaterial.
2. The preparation and photoelectric sensing application of the coal tar pitch carbon and carbon nitride composite material according to claim 1, characterized in that, In step one, the mass ratio of coal tar pitch, potassium carbonate and potassium chloride is 1:3:5, and 0.5 g of urea and 1 g of sodium hypophosphate are added for every 0.25 g of coal tar pitch; the mixing and grinding time is 30 minutes.
3. The preparation and photoelectric sensing application of the coal tar pitch carbon and carbon nitride composite material according to claim 1, characterized in that, In step one, the high-temperature calcination treatment involves heating to 700°C at a heating rate of 5°C / min under argon protection and holding at that temperature for 2 hours; the ethanol used for washing is 95% ethanol.
4. The preparation and photoelectric sensing application of the coal tar pitch carbon and carbon nitride composite material according to claim 1, characterized in that, In step two, the nitrogen-containing precursor is melamine or urea.
5. The preparation and photoelectric sensing application of coal tar pitch carbon and carbon nitride composite materials according to any one of claims 1 to 4, characterized in that, The composite material includes coal tar pitch-derived carbon and g-C3N4 nanosheets uniformly bonded to its surface, wherein the mass ratio of g-C3N4 to coal tar pitch-derived carbon is (5~9):(1~5), preferably 7:
3.
6. The preparation and photoelectric sensing application of the coal tar pitch carbon and carbon nitride composite material according to claim 5, characterized in that, As an application of electrode materials in the construction of photoelectrochemical sensors, photoelectrochemical sensors include working electrodes, counter electrodes, and reference electrodes.
7. The preparation and photoelectric sensing application of the coal tar pitch carbon and carbon nitride composite material according to claim 6, characterized in that, The method for preparing the working electrode includes: ultrasonically dispersing the composite nanomaterial, anhydrous ethanol, deionized water and Nafion solution into a uniform slurry, drop-coating it onto the cleaned FTO glass surface, and drying it at room temperature.
8. The preparation and photoelectric sensing application of the coal tar pitch carbon and carbon nitride composite material according to claim 7, characterized in that, Photoelectrochemical sensors for detecting Pb in water 2+ Cd 2+ Hg 2+ Applications of heavy metal ions.
Citation Information
Patent Citations
Preparation method and application of carbon nitride modified carbon nanotube composite material
CN114260020A
A hard carbon-nitrogen-phosphorus dual-doped nanocarbon composite carbon material and preparation method thereof
CN115663152B
Preparation method and application of heteroatom-doped porous carbon material
CN115995571A
Reduced graphene oxide / g-C3N4 composite material and preparation method thereof
CN118122391A